Prejudices and perceptions: patient acceptance of mobile technology use in health care. Issue 11 (November 2015) - Alexander, S. M.; Nerminathan, A.; Harrison, A.; Phelps, M.; Scott, K. M.
Abstract: mHealth is transforming health care, yet few studies have evaluated patient and carer perceptions of the use of smartphones at the patient bedside. In this study, 70 patients and carers answered a short survey on health professionals' use of mobile devices. Half the participants were tolerant of doctors using such devices if it was work‐related; others believed it was a distraction and not beneficial to patient care. Changes in practice and patient education may be needed to enable effective use of mobile devices in health.